Portuguese, French and British discourses on colonial education: Church-state relations, school expansion and missionary competition in Africa, 1890 - 1930 - Madeira, Ana Isabel (Paedagogica historica, 2005)
This article draws a comparison between the Portuguese in relation to British and French discourses on overseas educational policies at the turn of the nineteenth to the twentieth century until the 1930s. It focuses on three main colonial educational dynamics: school expansion (comparing the public and private sectors); State-Church relations (comparing these relationships at the European and colonial levels); and missionary competition (comparing Catholic with Protestant strategies towards educational incorporation). Colonial discourse is seen here as a power-knowledge discourse aimed at constructing the colonial subjects as individuals, enabling them to imagine themselves as belonging to a particular cultural polity. The article intends to show how cross-national discourses on education affect the principles on which theories of schooling are built and the ways in which they influence the first attempts to systematize pedagogical and school models in the colonial peripheries. On the other hand, it tries to understand, within government technologies of domination, the conflicting views, negotiations and ambiguities between global policy formulation and local school system implementation. In this sense, the author sought to analyse the different ways in which concepts such as 'assimilation', 'civilizing mission', 'adapted education', and 'learning by doing' were mobilized and appropriated into the colonial education discourses in order to legitimize particular governmental strategies. Two main ideas run through the text: the first attempts to demonstrate the existence of discontinuities between official educational ideologies at home and local system and school expansion strategies in the colonies. The second claims that educational borrowing from other colonies at the Empires' peripheries was, more often that is thought, a crucial feature of colonial educational discourse.